Molecular Identification, Compatibility and Shelf Life of Zinc and Silica Solubilizing Bacteria from Paddy Grown Soils - Babu, S. V.; Gopal, A. V.; Trimurtulu, N.; Babu, G. K.; Bhattiprolu, S. L. (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during January to October, 2019 at Advanced Post Graduate Centre, Acharya N.G. Ranga Agricultural University, Guntur, Andhra Pradesh, India to characterize and their compatibility and shelf-life of zinc and silica solubilizing bacteria, isolates from paddy soil. Thirty-two (32) zinc solubilising bacteria and 28 silica solubilising bacteria were isolated from paddy soil samples of 20 villages in Kurnool, Prakasam, Guntur and Anantapur districts of Andhra Pradesh, India. Two efficient zinc solubilizing bacteria were identified as Pseudomonas knackmussii B13 with 99.80% similarity (ZnKJJ-4) and Pseudomonas aeruginosa strain FQM with 99.66% similarity (ZnPGG-1); two efficient silica solubilizing bacteria were as Bacillus mucilaginosus strain CGMCC 1.2326 with 99.95% similarity (SiKPP-1) and Bacillus megaterium PSB1 with 99.92% similarity (SiPYY-3) by using 16S rRNA phylogenetic study, plant growth promoting properties and biochemical characteristics. The sequenced isolates were submitted to the NCBI-GenBank, and obtained the accession numbers NR121733.1 (ZnKJJ-4), MF144507.1 (ZnPGG-1), FJ009518.1 (SiKPP-1) and MW020222.1 (SiPYY-3). Shelf-life studies using different carrier materials (Lignite, peat and charcoal powder) in the incubator at 25°C revealed that Zinc solubilizing bacterial isolates survived better in lignite whereas Silica solubilizing bacterial isolates persisted in charcoal powder. Compatibility of the isolates was verified in the form of perpendicular streaks at the interaction zone in nutrient agar medium after 48–72 h at 28°C prior to evaluation in direct sown paddy crop.